2022
DOI: 10.3390/rs14184492
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Effect of Urban Green Spaces on Surface Urban Heat Island during Summer Period on an Example of a Medium Size Town of Zvolen, Slovakia

Abstract: Climate change affects the urban population’s health and quality of life. Urban green spaces (UGS) underpin several essential ecosystem services, amongst them climate regulation. Urban vegetation mitigates high temperatures and, thus, reduces the heat stress for urban residents. The study aimed to verify whether the Surface Urban Heat Island (SUHI) effect manifests itself even in a medium size town (Zvolen, Slovakia) surrounded by agricultural and forested landscape and to quantify the temperature mitigating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…In our previous paper [48], we confirmed the existence of an urban heat island even within a medium city with a large proportion of forest in its vicinity, as well as a cool island effect of urban green spaces within the city. However, we did not investigate the difference between the structure and size of each urban green space's area nor the spatial extent of their influence as crucial parameters for the effective management of the urban climate.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In our previous paper [48], we confirmed the existence of an urban heat island even within a medium city with a large proportion of forest in its vicinity, as well as a cool island effect of urban green spaces within the city. However, we did not investigate the difference between the structure and size of each urban green space's area nor the spatial extent of their influence as crucial parameters for the effective management of the urban climate.…”
Section: Introductionsupporting
confidence: 77%
“…The most significant cooling effect is provided by large (over 1 ha) green spaces with trees (GTl), where the cooling intensity (difference of LST compared to an urban area without vegetation) was almost 4.5 • C on average (maximum almost 6 • C) and the cooling distance was significant up to 90 m (less significant up to 180 m). As mentioned above, GGl and GTm have similar effects, with a higher cooling intensity (2.9 • C versus 2.5 • C on average) for GGl; however, the cooling effect (cooling distance) extends to a greater distance (up to 90 m) for GTm compared to GGl, where the cooling effect only extends to 30-60 m. Small areas with trees (GTs) and medium and small areas without trees (GGm and GGs) have an average cooling intensity below 2 • C; for GGm and GGl, this is even below 1.7 • C. This is the threshold below which the differences should already be evaluated with some caution due to the accuracy of LST determination using the Single-Channel Algorithm from Landsat imagery [48]. For GTs, their cooling effect on their surroundings was significant and extends to at least 60 m. For GGm and GGs, their cooling effect their surroundings was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the effectiveness of green spaces in mitigating the UHI effect can be improved by optimizing the size and shape of parks when designing and planning urban parks [107][108][109]. It has been shown that urban thermal environments can be improved through orderly planning of green infrastructure and management of long-term performance, which can mitigate the heat island effect [110][111][112] and slow down the rate of urban sprawl, leading to some reduction in temperature [113][114][115].…”
Section: Urban Form 431 Urban Green Space and Healthmentioning
confidence: 99%
“…Thus, green city areas have significant advantages in reducing the UHI. Meanwhile, in the study of green city areas and UHI [32], the effective cooling distance of green city areas is a key indicator for evaluating the effectiveness of green city areas in mitigating the UHI [33,34]. Therefore, accurate estimation of the range of green city areas cooling is crucial.…”
Section: Introductionmentioning
confidence: 99%